Green Entrepreneurs' Role in Food Security within the Green Economy in the Deli Serdang Case - Bunga Aditi; Suginam , Suginam; Cen, Cia Cai (CV Raskha Media Group, 2025)
This study aims to examine the role of green entrepreneurs in promoting food security based on a green economy in Deli Serdang Regency. Food security is a strategic national issue requiring innovative and sustainable approaches, especially in the face of climate change, environmental degradation, and socio-economic dynamics. Green entrepreneurship is considered an alternative solution that not only focuses on profit but also integrates ecological and social values into its business practices. This research employs a descriptive qualitative approach through a case study of several green entrepreneurs engaged in organic agriculture and the use of home gardens. The findings indicate that green entrepreneurs play a crucial role in community education, increasing access to healthy food, and promoting sustainable, community-based farming practices. Strategies employed include environmentally friendly product innovation, the integration of appropriate technology, and collaboration with local farmer groups. The study concludes that green entrepreneurship makes a tangible contribution to strengthening local food security and supports the transition toward an inclusive and sustainable green economy. The limitation of this research lies in its narrow geographical scope, suggesting the need for further studies across broader regions